Orbita the project = Orbita : proekt - Chanin, Semën 1970-; Svetlov, Vladimir 1973-; Timofejev, Sergej; Punte, Artūrs 1977- (Arc Publications, 2018)
"Orbita, founded in Riga [Latvia] in 1999, is a collective of Latvian poets writing in Russian whose unique work plays at the boundaries between various creative genres and cultures. This volume combines poetry, translation, imagery, web technologies, video and sound to offer a diverse introduction to Orbita's innovative art"--
Keywords: Concrete poetry; Visual poetry; Latvian poetry (Russian); Poets, Latvian; Russian poetry / Latvian authors; Russian poetry / Latvian authors / Translations into English; Poésie concrète; Poésie visuelle; concrete poetry; visual poetry; Translations; Anthologie